Análise e desenvolvimento de sistemas embarcados para auxílio ao diagnóstico de doenças na Atenção Primária à Saúde - Ferreira, Matheus André Coutinho (2021)
Introduction: The Unified Health System (SUS) has in Primary Health Care (PHC) the ordering of health care for SUS users. In the area of health, the implementation and use of systems is singularly critical due to the precariousness of infrastructure, low computerization of services and consequently the lack of information for decision making. Problem: Specialized professionals and high-cost equipment are essential for the diagnosis. In most PHC services, there are no adequate tools for screening and beginning of disease investigation, the resolution of the problems attended at this level of care is compromised, causing the cascading effect in the sectors responsible for the problems of medium and high complexity. Methodology: It was based in part on the Scrum framework for project management whose purpose was to promote the analysis and monitoring of the development of embedded systems. Initially, requirements were surveyed with professionals from various areas of knowledge, in order to understand the needs that the system should address, prototyping for validation of requirements, as well as to present the visual identity of the project. Finally, starting database modeling using the PostgreSQL database manager system, implementing the user interface and analyzing embedded systems. Results and discussions: This study provided support for the development and analysis of embedded systems of high specificity, low cost and rapid execution, in addition to the criteria of applicability and scalability for the Unified Health System (SUS), in addition to having interoperability with the patient's electronic medical record (PEP), ensuring the optimization of information management to public health services. Conclusion: The embedded systems developed and analyzed presented benefits related to diagnosis, optimization of the follow-up process throughout the patient's life, generation of indicators for decision making and cost reduction. This fact contributes to the induction of public policies and actions of the Ministry of Health.